Transrectal high‐intensity focused ultrasound (HIFU) for management of rectosigmoid deep infiltrating endometriosis: results of Phase‐I clinical trial. (1st September 2020) - Philip, C.‐A.; Warembourg, S.; Dairien, M.; Lefevre, C.; Gelet, A.; Chavrier, F.; Guillen, N.; Tonoli, H.; Maissiat, E.; Lafon, C.; Dubernard, G.
ABSTRACT: Objectives: Deep infiltrating endometriosis (DIE) of the rectosigmoid is associated with painful symptoms. When medical treatment is ineffective, surgical resection remains the standard treatment, despite significant risk of adverse events. High‐intensity focused ultrasound (HIFU) is a minimally invasive ablative procedure. Focal One® is a transrectal HIFU (TR‐HIFU) device used in prostate cancer treatment. The primary objective of this study was to confirm the feasibility of treatment with TR‐HIFU in patients presenting with posterior DIE with rectosigmoid involvement. We also assessed its safety and clinical efficacy in this context. Methods: This was a non‐controlled, prospective, Phase‐I clinical trial in a French University Hospital which is a multidisciplinary center for management of endometriosis. Included were patients older than 25 years, without plans to conceive within 6 months, who presented with a single lesion of posterior DIE, with rectosigmoid invasion, after failure of hormonal therapy. All lesions were assessed preoperatively using transvaginal sonography and magnetic resonance imaging. Patients completed questionnaires on gynecological and intestinal symptoms (similar to a visual analog scale (VAS)), and on quality of life (Medical Outcomes Study 36‐item short‐form survey (SF‐36) and, for the second half of patients recruited, symptom scoring system for constipation (KESS), female sexual function index (FSFI) and endometriosis health profile short‐version score (EHP‐5)), before, and at 1, 3 and 6 months after, TR‐HIFU treatment with a Focal One real‐time ultrasound‐guided HIFU device. Results: Twenty‐three consecutive patients were included in the study between September 2015 and October 2019. All 23 lesions were visualized, giving a detection rate of 100%. Twenty lesions were treated ('feasibility rate', 87.0%): in 13 the whole lesion was treated and in seven the lesion was treated partially. The mean duration of the TR‐HIFU procedure was 55.6 min. We observed a significant improvement in VAS score at 6 months, with differences relative to preoperative scores as follows, for: dysmenorrhea (–3.6, P = 0.004), dyspareunia (–2.4, P = 0.006), diarrhea (–3.0, P = 0.006), constipation (–3.0, P = 0.002), dyschezia (–3.2, P = 0.003), false urge to defecate (–3.3, P = 0.007), posterior pelvic pain (–3.8, P = 0.002) and asthenia (–3.8, P = 0.002). There was also a significant improvement in the SF‐36 score, with an increase at 6 months relative to the preoperative score in both the physical component summary (+ 9.3%, P = 0.002) and mental component summary (+ 10.9%, P = 0.017). No major complications occurred during or after any procedure. Conclusions: TR‐HIFU therapy for posterior DIE is feasible. If its efficacy and safety are confirmed, it could be a minimally invasive alternative to surgery for the treatment of rectosigmoid endometriosis. © 2019 Authors. Ultrasound in Obstetrics & Gynecology published by John Wiley & Sons Ltd on behalf of International Society of Ultrasound in Obstetrics and Gynecology.